PROTO-ICELAND PLUME CAUSED THINNING OF IRISH LITHOSPHERE - Landes M.; Ritter J.R.R.; Readman P.W. (My University, 2007)
The lithosphere–asthenosphere boundary (LAB) separates the rigid lithospheric plates from the hot convective mantle. In the region of the North Atlantic this boundary is widely influenced by the spreading head of the proto-Iceland plume [P. Kumar et al., The lithosphere–asthenosphere boundary in the North-West Atlantic region, Earth Planet. Sci. Lett. 236 (2005) 249–257.] that also caused the evolution of the British Tertiary volcanic province (BTVP) with the Giant's Causeway basalts as famous landmark. Using teleseismic shear-wave receiver functions we map the LAB underneath Ireland and find a distinctive lithospheric thinning of about 30 km towards the northern part of the island. As this region is part of the BTVP, we explain the lithospheric thinning, in agreement with geochemical results, by thermal erosion originating from the head of the proto-Iceland plume.
Keywords: IRELAND; LAB; RECEIVER FUNCTIONS